2002
DOI: 10.1523/jneurosci.22-24-10847.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rostral Ventromedial Medulla Neurons That Project to the Spinal Cord Express Multiple Opioid Receptor Phenotypes

Abstract: The rostral ventromedial medulla (RVM) forms part of a descending pathway that modulates nociceptive neurotransmission at the level of the spinal cord dorsal horn. However, the involvement of descending RVM systems in opioid analgesia are a matter of some debate. In the present study, patch-clamp recordings of RVM neurons were made from rats that had received retrograde tracer injections into the spinal cord. More than 90% of identified spinally projecting RVM neurons responded to opioid agonists. Of these neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
76
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 42 publications
11
76
1
Order By: Relevance
“…In vitro RVM recordings have shown that a large proportion of spinally projecting neurons respond directly to -opioid receptor (MOR) agonists, 19 which confirms the central role of the brainstem in opioid analgesia. 20,21 Moreover, many MOR-expressing spinally projecting neurons in the RVM stain positive for tryptophan hydroxylase, a marker of 5-HT content, and like-wise, many tryptophan hydroxylase-positive spinally projecting neurons respond to MOR agonists.…”
Section: Descending Modulatory Pathwaysmentioning
confidence: 87%
“…In vitro RVM recordings have shown that a large proportion of spinally projecting neurons respond directly to -opioid receptor (MOR) agonists, 19 which confirms the central role of the brainstem in opioid analgesia. 20,21 Moreover, many MOR-expressing spinally projecting neurons in the RVM stain positive for tryptophan hydroxylase, a marker of 5-HT content, and like-wise, many tryptophan hydroxylase-positive spinally projecting neurons respond to MOR agonists.…”
Section: Descending Modulatory Pathwaysmentioning
confidence: 87%
“…Because all three classes of opioid receptors are expressed in 5-HT neurons (4,31,32), it remains to be determined to what degree and in what way the loss of each individual opioid receptor in 5-HT neurons may have contributed to the altered behavioral phenotype of Lmx1b f/f/p mice. Obviously, it is possible that the attenuation of morphine analgesia in Lmx1b f/f/p mice could be due to a secondary change of MOR expression in other regions of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of the central 5-HT system in opioid analgesia is less clear. For the past several decades numerous pharmacological and behavioral studies have indicated that morphine-induced descending inhibition of nociceptive transmission depends on supraspinal 5-HT neurons (2)(3)(4). Despite these studies, many contradictory results concerning the role of central 5-HT neurons in morphine analgesia have also been reported, making it a long-standing controversial issue in pain research (5).…”
mentioning
confidence: 99%
“…Descending serotonergic pathways can be activated by ascending pathways involving neurokinin 1 receptor-positive projection neurons (Suzuki et al, 2002). Previous studies using combined electrophysiological and immunohistological approaches indicate that serotonergic descending pathways can also be disinhibited by MOR agonists (Marinelli et al, 2002). Disinhibition has a potentially rapid onset that could correspond well to the time course of the presently described immediate-onset facilitation.…”
Section: Withdrawal Ltp By Remifentanil Fentanyl and Morphinementioning
confidence: 73%
“…MORs are also expressed on neurons in various brain areas, including the rostral ventromedial medulla, that send descending projections to the spinal cord (Marinelli et al, 2002). MOR agonists may activate descending pathways that modulate spinal nociception.…”
Section: Introductionmentioning
confidence: 99%